2013
DOI: 10.1002/jmri.24399
|View full text |Cite
|
Sign up to set email alerts
|

Statistical analysis of multi-b factor diffusion weighted images can help distinguish between vasogenic and tumor-infiltrated edema

Abstract: Discrimination between tumor-infiltrated edema and vasogenic edema can be achieved by means of a 90-s multi-b factor diffusion-weighted sequence and factorial analysis. Simplified visual and quantitative interpretation of the results should also allow integration of multi-b factor analysis into routine neuroradiology practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 41 publications
(50 reference statements)
0
3
0
Order By: Relevance
“…DWI has been applied for the assignment of tumor grades or differentiation of tumors, as well as for the diagnosis of ischemic stroke [5,[10][11][12][13][14][15][16]19]. Several investigators found an inverse correlation between the ADC calculated from DW images and tumor cellularity [5,[13][14]16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…DWI has been applied for the assignment of tumor grades or differentiation of tumors, as well as for the diagnosis of ischemic stroke [5,[10][11][12][13][14][15][16]19]. Several investigators found an inverse correlation between the ADC calculated from DW images and tumor cellularity [5,[13][14]16].…”
Section: Discussionmentioning
confidence: 99%
“…The high sensitivity and specificity of DWI in the diagnosis of acute cerebral infarction is widely accepted. Also, DWI has a diagnostic potential to evaluate brain tumors by using the ADC values [10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…In DWI, a loss of image intensity of each voxel reflects the rate of microscopic water diffusion (apparent diffusion coefficient). DTI evaluates the preferred direction of HGG infiltration by different tensor metrics, some of which are robust, such as fractional anisotropy or the mean diffusivity index, and some use new mathematic algorithms for better sensitivity and specificity[28]. As HGG preferentially spreads along the white matter tracks, this ability to “image” tissue infiltration could be complementary to the perfusion/permeability metrics, which visualize only angiogenesis.…”
Section: New Concepts and New Technologies Are Promisingmentioning
confidence: 99%